Review on hydrometallurgical recovery of rare earth metals - Jha, M.; Kumari, A.; Panda, R.; Rajesh Kumar, J.; Yoo, Kyoungkeun; Lee, J. (Elsevier, 2016)
Rare earth metals are essential ingredients for the development of modern industry as well as designing and developing high technology products used in our daily lives. Consequently, the worldwide demand of rare earth metals is rising quickly and predicted to surpass the supply by 40,000 tons annually. However, their availability is declining, mainly due to the export quotas imposed by the Chinese government and actions taken against illegal mining operations. This has laid emphasis to exploit and expand technologies to meet the future necessities of rare earth metals. Bastnasite, monazite, and xenotime are their chief mercantile sources, which are generally beneficiated by flotation, gravity or magnetic separation processes to get concentrates that are processed using pyro/hydrometallurgical routes. To develop feasible and eco-friendly processes, R&D studies are being conducted for the extraction of rare earth metals from leached solutions (chloride, nitrate, sulfate, thiocyanate, etc.) using different cationic, anionic and solvating solvents or ions depending on material and media. Commercial extraction of rare earth metals has been carried out using different extractants viz. D2EHPA, Cyanex 272, PC 88A, Versatic 10, TBP, Aliquat 336, etc. The present paper reviews the methods used for the recovery of rare earth metals from primary as well as secondary resources, with special attention to the hydrometallurgical techniques, consisting of leaching with acids and alkalis followed by solvent extraction, ion exchange or precipitation. The piece of comparative and summarized review will be useful for the researchers to develop processes for rare earth recovery under various conditions.